NASKAH FILM ANIMASI “MASA KECILKU DENGAN DUNIA LAINKU” Menggunakan Teori 3-Act-Structure - Muhammad Prayoga; Evaliata Br Sembiring (Politeknik Negeri Batam, 2022)
Animated films are one of the entertainment media displayed by electronic devices such as televisions, computers, and smartphones. Animated films can also be used as a good learning medium to convey moral messages that can be addressed to all people from children to adults. In making animated films, it is necessary to write a script as the basic concept of making animated films. Script writing is the process of writing a story into a film scenario that contains story ideas, premise, plot, audio, storyline which are important in making animated films. The manuscript uses the 3-Act-Structure theory and was made using the Celtx application, then the feasibility of its production was analyzed. The animated film scripts produced are scripts and storyboards. The results of manuscript analysis based on 3-Act-Structure reached 80%, meaning that it met the criteria very well so it was feasible to be produced.